Baboon Envelope Pseudotyped “Nanoblades” Carrying Cas9/gRNA Complexes Allow Efficient Genome Editing in Human T, B, and CD34+ Cells and Knock-in of AAV6-Encoded Donor DNA in CD34+ Cells - Gutierrez-Guerrero, Alejandra; Abrey Recalde, Maria Jimena; Mangeot, Philippe E.; Costa, Caroline; Bernadin, Ornellie; Périan, Séverine; Fusil, Floriane; Froment, Gisèle; Martinez-Turtos, Adriana; Krug, Adrien; Martin, Francisco; Benabdellah, Karim; et al. (Frontiers in Genome Editing, 2021)
Programmable nucleases have enabled rapid and accessible genome engineering in eukaryotic cells and living organisms. However, their delivery into human blood cells can be challenging. Here, we have utilized “nanoblades”, a new technology that delivers a genomic cleaving agent into cells. These are modified Murine Leukemia Virus (MLV) or HIV-derived virus-like particle (VLP), in which the viral structural protein Gag has been fused to Cas9. These VLPs are thus loaded with Cas9 protein complexed with the guide RNAs. Highly efficient gene editing was obtained in cell lines, IPS and primary mouse and human cells. Here, we showed that nanoblades were remarkably efficient for entry into human T, B and HSPCs thanks to their surface co-pseudotyping with baboon retroviral and VSVG envelope glycoproteins. A brief incubation of human T and B cells with nanoblades incorporating two gRNAs resulted in 40% and 15 % edited deletion in the Wiskott Aldrich Syndrome (WAS) gene locus, respectively. CD34+ cells (hematopoietic stem and progenitor cells, HSPCs) treated with the same nanoblades allowed 30-40% exon1 drop-out in the WAS gene locus. Importantly, no toxicity was detected upon nanoblade-mediated gene editing of these blood cells. Finally, we also treated HSPCs with nanoblades in combination with a donor-encoding rAAV6 vector resulting in up to 40 % of stable expression cassette knock-in into the WAS gene locus. Summarizing, this new technology is simple to implement, shows high flexibility for different targets including primary immune cells of human and murine origin, is relatively inexpensive and therefore gives important prospects for basic and clinical translation in the area of gene therapy.